Synthesis of the New High Entropy Alloy and Its Application in Energy Conversion and Storage - Zhou, Heting; He, Jiangwei (Frontiers in Energy Research, 2020)
In order to explore the methods of energy saving and promoting energy regeneration, this paper presents the synthesis and application of new high energy alloy materials in energy conversion and storage. A new type of high entropy alloy material was prepared by analyzing its high strength, tempering resistance and softening resistance. The electrochemical properties of the new type of high entropy alloy were studied according to its microstructure and as cast structure. The experimental results show that compared with fesn2, the new high entropy alloy material has greater advantages in capacity, electrochemical performance, capacity stability and magnification in the process of cyclic charging, at low annealing temperature, the solid Co nanoparticles are further transformed into hollow Co3O4 nanospheres by the kirkentel effect on the nanoscale. NC- Co3O4 nanocomposites as zinc air battery cathodes exhibit excellent OER and ORR properties: low overpotential 352 mv, high initial reduction potential 0.91 v and half wave potential 0.87 v, high open circuit voltage 1.44 v, capacitance 387.2 mah/g and excellent cycle stability. Nico bimetallic phosphide nanotubes derived from the high entropy alloy-74 are efficient electrocatalysts for water decomposition.